2016
DOI: 10.5056/jnm15192
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Proton Pump Inhibitor for Survival in Patients with Gastroesophageal Reflux Disease and Idiopathic Pulmonary Fibrosis

Abstract: Background/Aims The prevalence of gastroesophageal reflux disease (GERD) is high in patients with idiopathic pulmonary fibrosis (IPF). GERD may cause chronic microaspiration that leads to repeated subclinical lung injury, which leads to pulmonary fibrosis. Although some studies have suggested that proton pump inhibitors (PPI) were associated with a good prognosis in IPF, their effects remain unclear. Methods We retrospectively reviewed 786 consecutive adult patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 28 publications
1
55
0
Order By: Relevance
“…We read with great interest the paper by Lee et al 1 on the protective effect of proton pump inhibitors (PPIs) for survival in patients with gastroesophageal reflux disease (GERD) and idiopathic pulmonary fibrosis (IPF). The Authors reviewed a very large number of consecutive adult patients with IPF (n = 786) and concluded that the prevalence of GERD is lower in Korean patients than in other countries and that PPI use for at least 4 months may have a protective effect against IPF-related mortality.…”
Section: To the Editormentioning
confidence: 95%
“…We read with great interest the paper by Lee et al 1 on the protective effect of proton pump inhibitors (PPIs) for survival in patients with gastroesophageal reflux disease (GERD) and idiopathic pulmonary fibrosis (IPF). The Authors reviewed a very large number of consecutive adult patients with IPF (n = 786) and concluded that the prevalence of GERD is lower in Korean patients than in other countries and that PPI use for at least 4 months may have a protective effect against IPF-related mortality.…”
Section: To the Editormentioning
confidence: 95%
“…Lee et al . evaluated that patients with IPF who were treated for more than 4 months of PPI had a lower mortality rate . PPIs may directly inhibit the migration and interaction between inflammatory and endothelial cells.…”
Section: Aspiration and Gerd In Pulmonary Fibrosismentioning
confidence: 99%
“…100 Lee et al evaluated that patients with IPF who were treated for more than 4 months of PPI had a lower mortality rate. 111 PPIs may directly inhibit the migration and interaction between inflammatory and endothelial cells. Esomeprazole and lansoprazole suppress expression of inflammatory cytokines (tumor necrosis factor-␣, interleukin (IL)-1␤, IL-6, IL-8, adhesion molecules, fibronectin, and matrix metalloproteinase enzymes).…”
Section: Aspiration and Gerd In Pulmonary Fibrosismentioning
confidence: 99%
“…The prevalence of hiatal hernia, which is associated with reflux and erosive esophagitis, was also increased in patients with IPF compared with healthy controls or patients with asthma or chronic obstructive pulmonary disease [2022]. Studies reporting the prevalence of GERD and/or hiatal hernia are listed in Table 1 [10, 18, 1939]. …”
Section: The Prevalence Of Gerd In Ipfmentioning
confidence: 99%
“…The incidence of newly diagnosed GERD seems to be continuously increasing in patients with IPF [18]. A recent systematic review reported that 0–94% of patients with IPF suffer from GERD [7].…”
Section: The Prevalence Of Gerd In Ipfmentioning
confidence: 99%